High prevalence of exercise-induced laryngeal obstruction in a cohort of elite cross-country skiers - Irewall, T.; Bäcklund, C.; Nordang, L.; Ryding, M.; Stenfors, N. (Medicine & Science in Sports & Exercise, 2021)
Introduction: Exercise-induced laryngeal obstruction (EILO) is a differential diagnosis for asthma and prevalent in athletes referred for exercise-induced dyspnea. The aim of this study was to estimate the prevalence of EILO in elite cross-country skiers, known for a high prevalence of asthma. Method: Elite cross-country skiers were invited for screening of EILO. Screening consisted of clinical assessment, questionnaires, skin prick test, spirometry, eucapnic voluntary hyperventilation test, and continuous laryngoscopy during exercise test. Current asthma was defined as physician-diagnosed asthma and use of asthma medication during the last 12 months. EILO was defined as =2 points at the supraglottic or glottic level during exercise at maximal effort, using a visual grade score system. Result: A total of 89 (51% female) cross-country skiers completed the study. EILO was identified in 27% of the skiers, 83% of whom were female. All skiers with EILO had supraglottic EILO, and there was no glottic EILO. Current asthma was present in 34 (38%) of the skiers, 10 (29%) of whom had concomitant EILO. In the skiers with EILO, a higher proportion reported wheeze or shortness of breath after exercise, compared with skiers without EILO. In skiers with EILO and current asthma, compared with skiers with asthma only, a higher proportion reported wheeze or shortness of breath after exercise. Asthma medication usage did not differ between these groups. Conclusion : EILO is common in elite cross-country skiers, especially females. Asthma and EILO may coexist, and the prevalence of respiratory symptoms is higher in skiers with both. Testing for EILO should be considered in cross-country skiers with respiratory symptoms.